Effects of occlusal adjustment on clinical success of non carious cervical restoration's - Ghavam Nasiri M.; Goharian R.; Madani A.; Salari. T. (Tehran University of Medical Sciences, 2004)
Statement of Problem: Parafunctional habits are the most important factor in the creation of non-carious cervical lesions and correcting of these habits may affect cervical lesions. Purpose: The goal of this study was to survey the effects of one-year occlusal adjustment on clinical success of non- carious cervical restorations. Materials and Methods: In this clinical study, sixty tooth-colored cervical restorations on canines and premolars in patients with parafunctional habits (bruxism and clenching) were studied. The teeth, according to the type of restorative material, were randomly divided into two groups: One group with a composite resin (Tetric Flow; Group A: n=30) and the other group with a compomer (Compoglass Flow; Group B: n=30). After restoration, each group was divided into two subgroups: (A1, B1) with occlusal adjustment (case group), (A2, B2) without occlusal adjustment (control group). The evaluation was perfumed single blind at 6 and 12 months after restorative operations according to Us Public Health Service (USPHS) classification. Assessment criteria included: marginal integrity, marginal discoloration, recurrent caries, postoperative sensitivity and loss of filling. Statistical analysis was completed using Fisher's exact test. Results: In 12 month period between two groups of compoglass Flow restorations, group B1 showed superior results than group B2, however, no significant difference was found between both groups of tetric flow restorations (A1 and A2). There was also no difference in clinical conditions between A2 and B2 groups. Conclusion: Considering the results of this study, it can be concluded that occlusal adjustment puts a considerable effect on clinical success of compoglass non- carious cervical restorations. However, it should be mentioned that such and effect was not found among Tetric flow restoration.